The study of English literature from a Tawhidic framework - Mohd Ramli, Aimillia (2014)
The objective of this paper is to suggest a new framework for the study of English literature that integrates traditional Islamic scientific and humanistic philosophical approaches on the spirit. This framework involves the application of Quranic verses and hadith as well as the Islamic theology and philosophy of several Muslim figures, notably Syed Muhammad Naquib al-Attas and Muhammad Iqbal, on a number of issues, such as intuition, free-will and happiness. These will then be applied to comparative analyses of English and Islamic literature by writers and poets. Other methods used could be the comparative religion framework, particularly for English literary works that deal with Christianity. By locating literature as having an important role in Western-Islamic comparative studies of scientific philosophy and theology, this paper suggests a new education and role for future literary critics as those who would be engaged in literary appreciation while propagating a Tawhidic framework for literary studies.